RANCANG BANGUN APLIKASI SISTEM DATABASE MATERIAL WAREHOUSE BERBASIS WEB PT PERTA-SAMTAN GAS PRABUMULIH - Permata, Dhea (Universitas Lambung Mangkurat, 2024)
PT Perta-Samtan Gas Prabumulih is a company engaged in the gas trading sector which is under the auspices of the Indonesian BUMN. The company has two processing plants, namely the Extraction Plant and the Fractionation Plant. Nationally, the two refineries greatly contribute to the supply of LPG, where all raw material inventory for factory operational goods is managed by the Warehouse. In processing the material database, the company still uses a simple application, namely Microsoft Excel. This is a problem, especially in the process of searching for material storage locations (locbins) that make employees take a long time to find the data they need. To obtain clearer information, the authors conducted research using a qualitative descriptive method. Where in this study the authors used two sources of data, namely, primary data and secondary data. In addition, data collection techniques were obtained from interview scripts and direct observation of the research object and by looking for references through books or journals. After conducting this research, the authors collected the data obtained and then the authors resolved the existing problems by producing a